ИССЛЕДОВАНИЕ ИНТЕГРАЛЬНОЙ ТОКОВОЙ ЧУВСТВИТЕЛЬНОСТИ СТРУКТУРЫ Al–Al2O3–p-CdTe–Mo - Утениязов, А.К.; Есенбаева, Э.С.; Аннаева, Ш.Х.; Нсанбаев, М.Т. (SCIENCE and SOCIETY, 2023)
The article presents the results of studies of the integral current sensitivity of the Al-Al2O3–p-CdTe-Mo structure when applying high voltages of shift in the forward direction of the current. It is shown that the studied structure of Al-Al2O3-p-CdTe-Mo in the forward direction of the current works as an injectional photodetector with internal amplification, which speed is equal to τ≈10-7-10-6s. It is established that the integral current sensitivity reaches the highest value of Sint Sint~1.4∙106 A/W when illuminated with white light with illumination E≈7.85∙10-7 lx and at V=7 V.
Keywords: integral current sensitivity; photosensitivity; injection; injection photoreceiver; photocurrent; illumination; offset voltage